1995
DOI: 10.1111/j.1600-0765.1995.tb01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis in the baboon: a potential model for human disease

Abstract: Advances in periodontics with respect to disease activity, microbiology and immunology have demonstrated the multifactorial nature of periodontal diseases. This serves to underscore the need for an ideal animal model for periodontal research. Non-human primates are most similar to man in comparison to other animal models. The baboon is an Old World monkey that has infrequently been used in periodontal research. Periodontal exams were accomplished on 116 baboons (Papio anubis, P. cynocephalus) ages 5 to 30 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
3
15
1
Order By: Relevance
“…Consistent with previous findings, 22 sex was not associated with periodontal disease in this baboon population. Females had slightly elevated levels of disease and were older compared to males, but sex was not significant after adjusting for age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous findings, 22 sex was not associated with periodontal disease in this baboon population. Females had slightly elevated levels of disease and were older compared to males, but sex was not significant after adjusting for age.…”
Section: Discussionsupporting
confidence: 92%
“…The animal population had been captive for various lengths of time and both captive and recently, wild‐caught baboons had similar amounts of disease. Although baboons are large‐bodied, terrestrial omnivores adapted to a wide range of environmental habitats from semidesert to woodland and require large amounts of food, they have long lives (up to 30 years or more in captivity) and similar patterns of dental diseases to humans 21,22 . In one study, periodontal examinations were performed on 116 baboons and significant increases with age were found in mean probing depths and mean attachment levels, with the conclusion being that the baboon may be a suitable model for studies of human periodontal disease 22 …”
mentioning
confidence: 99%
“…Owing to the difficulty of obtaining older animals with fully developed permanent dentitions, the experiments were conducted on the still completely firm deciduous teeth. Even though, contemporary research has shown few similarities, this study (Avery & Simpson, 1973;Aufdemorte et al, 1993;Miller et al, 1995;Rogers & Hixson, 1997;Weiner et al, 1999;Carr et al, 2000;Perel et al, 2007), used as reference for our clinical practice it didn't even use permanent teeth, they were deciduous, and to compare bone physiology findings, with humans, it does not show the same results as reported by a systematic review from Perel et al…”
Section: Introductioncontrasting
confidence: 43%
“…There is clear evidence that the various species of primates ( e.g. M. fascicularis, M. mulatta, M. nemestrina, S. scuireus, P. anubis ) all demonstrate naturally-occurring periodontal disease that increases with aging [Schou et al, 1993; Madden and Caton, 1994; Miller et al, 1995; Struillou et al, 2010; Oz and Puleo, 2011]. These species demonstrate clinical, microbiological, and immunologic similarities to the disease in humans.…”
Section: Introductionmentioning
confidence: 99%